The influence of financial socialization on young adults - Glenn, Christina Elaine (Kansas State University, 2018)
College is a time when many young adults are beginning to make financial decisions on their own. The financial behaviors they engage in can have effects on their academic success, life satisfaction, relationship quality, physical and mental well-being, and financial well-being. This dissertation examined the direct and indirect relationships between financial socialization, financial knowledge, financial self-efficacy, and financial behaviors in college students using data from the 2014 National Student Financial Wellness Study (NSFWS). The sample consisted of 12,598 college students from 52 college institutions. Structural Equation Modeling (SEM) was conducted with the tested model guided by Gudmunson and Danes’ (2014) Family Financial Socialization (FFS) conceptual framework. Results revealed financial socialization has a direct influence on financial knowledge, financial self-efficacy, and financial behaviors. An indirect association between financial socialization and financial behaviors through its association with financial self-efficacy was also found. Alternative models discovered neither parental financial socialization nor formal financial education alone impacted financial knowledge, but when combined, their influence became significant, suggesting a possible interaction effect between formal financial education and parental financial socialization. Objective financial knowledge was not found to influence financial self-efficacy or financial behaviors in college students. Results showed financial self-efficacy to be the strongest predictor of students engaging in positive financial behaviors. A one standard deviation increase in financial self-efficacy was associated with a 90% increase in the standard deviation of financial behavior. This study provides support and implications for the FFS conceptual framework. Financial counselors, advisors, and therapists can use these findings to educate their clients on the importance of financial socialization of their children. Furthermore, results reinforce the need for mandatory formal financial education and infer the importance of parents and educators working together to cultivate financial knowledge in children.
Keywords: financial socialization; financial self-efficacy; financial behavior; financial knowledge; college students